ANALISIS POTENSI EKOWISATA DALAM NEGELOLAAN SUMBERDAYA ALAM BERKELANJUTAN PADA KAWASAN HL BUKIT PANJANG RANTAU BAYUR (Studi : Dusun Lubuk Beringin Kecamatan Bathin III Ulu Kabupaten Bungo) - Eko Setianto; Hutwan Syarifuddin; Doni Iskandar (Universitas Jambi, 2019)
This study aims to identify the potential of ecotourism in the Bukit Panjang Rantau Bayur Protect Forest Area in Lubuk Beringin Hamlet and analyze ecotourism management strategies as an effort in sustainable natural resource management in the Bukit Panjang Rantau Bayur Protect Forest Area. Ecotourism potential is determined through observation, surveys and interviews with hamlet communities then the results are described qualitatively. Ecotourism strategy uses SWOT analysis. The results of this study indicate that there is potential for natural resources in the Bujang Raba protect forest area in Lubuk Beringin Hamlet which has the potential to be used as an object of natural tourist attraction, which includes the local wisdom of lubuk prohibit, Batang Buat River which has potential fish resources and rafting , Waterfalls, agroforests, Village Forests which have rich flora and fauna and socio-cultural tourism. The strategy of ecotourism activities in the Bujang Raba region which currently has obtained legality through village forests is carried out in a planned and sustainable manner, some natural tourist attraction object potentials are used as tour packages and make the local wisdom of the community as an icon in maintaining landscape cover by interweaving investment cooperation that has conservation value and establishes synergy and integration between stakeholders in building ecotourism in accordance with regional government policies.